The effect of zirconia thickness on the biaxial flexural strength of zirconia-ceramic bilayered discs - TARÇIN, BİLGE; SINMAZIŞIK, GÜLDEN (JAPANESE SOC DENTAL MATERIALS DEVICES, 2015)
The aim of this study was to assess the effect of zirconia core thickness on the biaxial flexural strength values of zirconia-porcelain bilayered discs. A total of 60 discs with 0.3, 0.4, and 0.5 mm thickness were obtained from a fully sintered zirconia block. A 1.5-mm thick layer of veneer porcelain was fired on the zirconia specimens and biaxial flexural strength tests were performed on the bilayered discs. In each group, the loading surface was the veneer porcelain in half of the specimens (core in tension) and the zirconia core surface in the other half (core in compression). The zirconia core thickness had no effect on the biaxial flexural strength of zirconia-porcelain bilayered discs when the core was in tension (p>0.05). Whereas, when the core was in compression, an increase in the zirconia core thickness resulted in an increase in the biaxial flexural strength (p<0.05).
Keywords: Biaxial flexural strength; Bilayered ceramic; Zirconia core thickness; FIXED PARTIAL DENTURES; INTERFACIAL SURFACE-ROUGHNESS; TZP DENTAL CERAMICS; IN-VITRO; CONNECTOR AREA; FRACTURE; FAILURE; MODE; RELIABILITY; CROWNS